Analysis of impact of group delay on slope distortion of S-curve in delay locked loop. (9th May 2021) - Liu, Yuqi; Ran, Yihang; Yang, Yi; Chen, Lin; Xiong, Tuling; Pan, Hongchen
Abstract: As essential specifications of correlation domain for signal quality evaluation, distortions of the S-curve, including bias and slope distortions of the zero-crossing point, are usually selected as indicators of optimisation in the process of designing the channels of receivers or navigation satellites. Focusing on this issue, we present a detailed analysis of slope distortion in the presence of group delay and amplitude distortions. After validating the theoretical results, we present further discussions about the impacts of different group delay terms on slope distortions. The results indicate that both the odd-order and the even-order terms have impacts on the slope distortion, and higher odd-order terms have less slope distortion compared with the lower odd-order terms. These results are useful for evaluating the slope distortion from the group delay and guiding improvement in design of the channel.